Blackfeet innovation pathways to food sovereignty: sustainability through indigenous-led research partnerships - Paul, Kimberly L.; Ruppel, Kristin T.; Young, Micaela M.; Caplins, Laura; Ramaker, Jill Falcon; Carter, Christopher J.; Seeley, William B.; Falcon, Christen; Berger, Andrew (Frontiers in Sustainable Food Systems, 2024)
The Blackfeet Nation in northwestern Montana, USA, is implementing its Agriculture Resource Management Plan (ARMP), an Indigenous-led, sustainable agriculture plan prioritizing economic development for Indigenous producers, intergenerational health and well-being of Amskapi Piikani Blackfeet people, and ecological and cultural sensitivities within this sovereign nation and its traditional territories. Since the passage of the American Indian Agricultural Resource Management Act of 1993, only three Tribes have drafted and finalized Agricultural Resource Management Plans (ARMPs). The Blackfeet ARMP is now being held up as a national model of Tribal sovereignty. "Blackfeet Innovation Pathways to Food Sovereignty", an Indigenous-led research project, emerged from the Blackfeet Nation's community-based strategic planning process identifying gaps, systemic barriers and impactful solutions for achieving Blackfeet food sovereignty through the implementation of the Blackfeet Nation ARMP, along with research influenced by the ARMP. This paper provides a community case study of the ongoing process and offers a translational model of sustainable agriculture and food sovereignty within Indigenous lands to improve the economic futures of producers and their families, as well as health outcomes for Native communities.